New records of spider wasps (Hymenoptera, Pompilidae) from Colombia - Castro-Huertas, Valentina (Pensoft Publishers, 2014)
Abstract. New records of genera and species of spider wasps (Hymenoptera: Pompilidae) from Colombia are provided. Agenioideus, Cryptocheilus, Evagetes, Mystacagenia, and Xerochares are newly recorded genera from Colombia. Nineteen species are first recorded from Colombia: Aimatocare vitrea (Fox); Ageniella azteca (Cameron); Ageniella curtipinus (Cameron); Ageniella fallax (Arlé); Ageniella hirsuta Banks; Ageniella pilifrons (Cameron); Ageniella pretiosa Banks; Ageniella sanguinolenta (Smith); Ageniella zeteki (Banks); Agenioideus birkmanni (Banks); Aporus (Aporus) cuzco Evans; Aporus (Cosmiaporus) diverticulus (Fox); Aporus (Notoplaniceps) canescens Smith; Euplaniceps exilis (Banks); Euplaniceps herbertii (Fox); Irenangelus clarus Evans; Mystacagenia bellula Evans; Phanochilus nobilitatus (Smith) and Xerochares expulsus Schulz. The following species and genera have their occurence ranges expanded for South America: Ageniella azteca (Cameron); Ageniella zeteki (Banks); Agenioideus birkmanni (Banks); and Xerochares expulsus Schulz; Cryptocheilus Panzer; and Xerochares Evans.